Aggressive surgical management of craniopharyngiomas - Singh, Manmohan; Chandra, P.S.; Sharma, B.S. (Indian Journal of Neurosurgery, 2013)
Surgical treatment of craniopharyngiomas is challenging and despite advancements it continues to pose a challenge. Proponents of subtotal resection in conjunction with radiotherapy argue that this less aggressive approach can yield appropriate results with the lower morbidity. On the contrary, other argument is that gross total resection is superior. Though surgical management of craniopharyngioma is challenging due to its location and important surrounding neurovascular structures, optimal surgical results can be expected following radical surgical excision. Radical excision of craniopharyngiomas is associated with excellent long-term recurrence free survival. Radiation induced long-term complications can be altogether avoided by excising these tumors completely.
Keywords: Craniopharyngioma; radical excision; surgical management of craniopharyngioma